Three Spiritual Taxonomies in Islamic Education - Affandi, Akhmad; Tehmamad, Abdulghani; Munjiat, Siti Maryam; Saidah, Zahrotus (Program Studi Pendidikan Agama Islam, 2025)
The taxonomy-based mechanistic approach in learning Islamic Religious Education and Character Education (PAI BP) risks reducing religiosity to mere ritual formalities, thereby hindering the growth of authentic, reflective, and transformative spiritual experiences. Therefore, it is necessary to develop a taxonomy that establishes the dimension of attitudes in PAI BP learning with a formulation that is not complex but rather simple and applicable. This research used a systematic literature review, specifically the PAI BP textbook, the PAI BP Teacher and Student Books, published by the Ministry of Education, Culture, Research, and Technology, which were analyzed objectively and systematically, and conclusions were drawn. This study offers the Three Spiritual Taxonomies in PAI BP learning. This taxonomy divides spirituality into three dimensions: understanding with the operational verb